Psychological Well-Being and Optimism-Pessimism of the Elderly People in Nursing Home: The Effect of Regular Intergenerational Visitation - Turen, Sevda; Toksöz, Fatma; Çerci, Seyhan; Yenisu, Edanur; ÇETİN, AYKE NİSA; Taşkın, Gülcan Batur (Wiley, 2025)
AimThis study was conducted to determine the impact of regular visits by Generation Z individuals on the psychological well-being and optimism-pessimism levels of elderly people in a nursing home.MethodsThe study employed a quasi-experimental design with a single group, utilising pre-test and post-test measurements. "Psychological Well-Being Scale," and the "Optimism-Pessimism Scale-Adult Form" were used. Study reported in accordance with STROBE Checklist.ResultsThe participants (n = 201) had a mean age of 72.40 +/- 7.72 years, with most residing in the nursing home for over 5 years. A significant difference was observed between the mean psychological well-being scores of participants before and after the visit. Also, there was a significant difference in the optimism-pessimism dimension scores on the Optimism-Pessimism Scale before and after the visit.ConclusionIt was established that regular intergenerational visits had a beneficial impact on the psychological well-being of the elderly in nursing homes, resulting in an increase in optimism and a reduction in pessimism.Relevance to Clinical PracticeIntergenerational programs are gaining more and more attention every day due to their potential to benefit young people, older people, and society. Thus, it may be possible to increase the social support levels of the elderly and prevent negative age discrimination.
Keywords: Elderly; Nursing Homes; Optimism; Pessimism; Psychological Well-being